Impact of Explicit and Visual Instructional Strategies on Vocational Interest of Pupils with Mild Intellectual Disability in Selected Schools in Ibadan, Nigeria (2011)
Vocational training is important in achieving economic empowerment and independence in persons with intellectual disability. However, pupils with intellectual disability often enter the labour market in Nigeria without receiving vocational training resulting into serious challenges to these pupils. Several existing research on pupils with intellectual disability focused on improving academic performance, while few studies have been done on enhancing their vocational interest using Explicit and Visual Instructional strategies. This study, therefore, investigated the impact of Explicit Instructional Strategy (EIS) and Visual Instructional Strategy (VIS) in enhancing the vocational interest of pupils with mild intellectual disability in Ibadan, Nigeria. The study adopted a pretest-posttest control group, quasi experimental research design with a 3x2 factorial matrix. Thirty primary five pupils with mild intellectual disability were purposively selected from three special schools for the handicapped in Ibadan, Oyo State, Nigeria. Selected pupils in each school were randomly assigned to the two experimental groups (EIS and VIS) and control group. Data were obtained using Slosson‘s Intelligence Test (r=0.86), Reading-Free Vocational Interest Inventory (r=0.90) and Socio-Economic Status Scale (r=0.87). Participants in the experimental groups were exposed to eight weeks of vocational interest training using EIS and VIS strategies. Five hypotheses were tested at 0.05 level of significance while data were analysed using descriptive statistics, t-test, Analysis of Covariance and Duncan post hoc test. The experimental groups (EIS and VIS) had higher vocational interest scores than those in the control group (F(2,29)=8.04; p<0.05). The Duncan post hoc test further showed that each of the three possible pairs of instructional groups was significantly different from one another (p<0.05). The group exposed to VIS had the highest post-test score (x=67.97) than the EIS (x=60.32) while the least post-test score was obtained by the control group (x=60.32). There was significant main effect of socio-economic status in enhancing vocational interest of pupils with intellectual disability (F(1,29)=4.454; p<0.05). Pupils with high socio-economic status background had higher vocational interest score ( x =65.73) than those with low socio-economic status. There was no significant effect of gender in enhancing of vocational interest of pupils with intellectual disability. The females obtained higher post-test mean score ( x =64.92) than their male counterparts ( x =64.04).Visual Instructional Strategy and Explicit Instructional Strategy were effective in enhancing the vocational interest of pupils with mild intellectual disability. Therefore, the two strategies should be adopted for use in enhancing vocational interest of pupils with intellectual disability, both in the general education classroom and in special education settings. Also, the government should organise in-service trainings like seminars, workshops and conferences for primary school teachers on the use of the instructional strategies in other to enhance the vocational interest of pupils with intellectual disability.